Solutions to the Calapso, Zoomeron, and Davey-Stewartson III Equations using Ribaucour Transformations - Lopes Ferro, Marcelo (2023)
In this paper, we present a method for obtaining solutions to the Calapso and Zoomeron equations using Ribaucour transformations. We provide explicit formulas for the solutions of these equations. By applying this method to the generalized cylinder, we provide new solutions of these equations, which are determined by a free function and by two other functions, each one defined in a given variable. As a consequence, we provide new solutions for the Davey-Stewartson III equation.